2007
DOI: 10.1111/j.1365-2982.2007.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional association between proximal and distal gastric motility during fasting and duodenal nutrient stimulation in humans

Abstract: A functional integration exists between proximal and distal gastric motor activity in dogs but has not been demonstrated in humans. To determine the relationship between proximal and distal gastric motor activity in humans. Concurrent proximal (barostat) and distal (antro-pyloro-duodenal (APD) manometry) gastric motility were recorded in 10 healthy volunteers (28 +/- 3 years) during (i) fasting and (ii) two 60-min duodenal infusions of Ensure((R)) (1 and 2 kcal min(-1)) in random order. Proximal and APD motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Slow fundic contractions are believed to transfer gastric contents from the fundus to the antrum for trituration and subsequent GE. These contractions might be affected by gastrostomy placement in the gastric body 21. To clarify the cause for delay in GE, motility tests such as three-dimensional ultrasonography or dynamic contrast-enhanced magnetic resonance imaging of the stomach may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Slow fundic contractions are believed to transfer gastric contents from the fundus to the antrum for trituration and subsequent GE. These contractions might be affected by gastrostomy placement in the gastric body 21. To clarify the cause for delay in GE, motility tests such as three-dimensional ultrasonography or dynamic contrast-enhanced magnetic resonance imaging of the stomach may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen and co-workers observed a functional association between the fundic squeeze and the antral contraction waves for both the fasting and the fed stomach. 120 The antral contraction waves originate from pacesetter cells (so-called interstitial cells of Cajal) at the greater curvature of the middle corpus. Within 60 s, peristaltic waves progress along the gastric wall toward the pylorus with velocities of around 2 to 3 mm/s and mean occlusion rates of 40% to 60%.…”
Section: ■ Processing Of Food In the Oral Cavitymentioning
confidence: 99%
“…A number of previous studies reported that duodenal nutrients or distension reduced proximal gastric tone, delayed gastric emptying, and increased pyloric contractions (17,32). Colon-rectal distension has been reported to induce delayed gastric emptying (20,31), abnormalities of gastric slow waves (1,21), and inhibition of proximal gastric tone (12).…”
Section: Effects Of Electrical Stimulation On Slow Waves and Optimal mentioning
confidence: 99%